The Relationship Between the Personality Competencies of Islamic Religious Education Teachers With Discipline, Student Morals in School, and Student Responsibilities - Deni Tata Kusuma; Tedi Priatna; Supiana Supiana; Marus As’ad (Riviera Publishing, 2025)
This research is motivated by student morale which is influenced by several factors, one of which is the personality competence of teachers, especially Islamic Religious Education (PAI) teachers. To improve the competence of teachers in schools, especially the performance of PAI teachers, it is not enough to just deliver lessons face-to-face in the classroom, but the personality competencies of PAI teachers must be able to build discipline attitudes, student morale at school, and a sense of student responsibility. This study aims to determine the relationship between the personality competencies of PAI teachers and discipline, student morale at school, and student responsibilities in SMA Negeri 1, 3, and 4 Bandung City. This research departs from the framework of thinking that the personality competence of teachers, especially PAI teachers, greatly determines students' attitudes and behaviors as role models both in the school environment and in the community. The methods used were quantitative associative descriptive methods and surveys, with 120 respondents selected using simple proportional and random sampling techniques. Data collection using Google Form instruments was then analyzed by simple correlation, partial correlation, and multiple regression. The results of the study show that the personality competence of PAI teachers has a positive and significant effect on student discipline, morals, and responsibilities. The competence of a good PAI teacher's personality can improve students' attitudes of discipline, morals, and sense of responsibility at school, although the effect varies from school to school. External factors such as the social environment, school culture, and interaction between students also affect student behavior. Therefore, the development of teacher competencies must be balanced with the creation of a supportive school environment so that the formation of students' character can run optimally.